Malvinas Current variability from Argo floats and satellite altimetry - Artana, Camila Indira; Ferrari, Ramiro; Koenig, Zoé; Saraceno, Martin; Piola, Alberto Ricardo; Provost, Christine (Journal of Geophysical Research: Oceans)
The Malvinas Current (MC) is an offshoot of the Antarctic Circumpolar Current (ACC). Downstream of Drake Passage, the northern fronts of the ACC veer northward, cross over the North Scotia Ridge (NSR) and the Malvinas Plateau, and enter the Argentine Basin. We investigate the variations of the MC circulation between the NSR and 41°S and their possible relations with the ACC circulation using data from Argo floats and satellite altimetry. The data depict meandering and eddy shedding of the northern ACC jets as they cross the NSR. The altimetry fields show that these eddies are trapped, break down, and dissipate over the Malvinas Plateau, suggesting that this region is a hot spot for dissipation of mesoscale variability. Variations of sea level anomalies (SLA) across the NSR do not impact the MC further north, except for intra-seasonal variability associated with coastal trapped waves. Altimetry and float trajectories show events during which a large fraction of the MC is cut off from the ACC. Blocking events at around 48.5°S are a recurrent feature of the MC circulation. Over the 23 year altimetry record, we detected 26 events during which the MC surface transport at 48.5°S was reduced to less than half its long-term mean. Blocking events last from 10 to 35 days and do not present any significant trend. These events were tracked back to positive SLA that built up over the Argentine Abyssal Plain. Future work is needed to understand the processes responsible for these blocking events. Fil: Artana, Camila Indira. Universite de Paris VI; Francia. Centre National de la Recherche Scientifique; Francia Fil: Ferrari, Ramiro. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Centro de Investigaciones del Mar y la Atmósfera. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Centro de Investigaciones del Mar y la Atmósfera; Argentina Fil: Koenig, Zoé. Universite de Paris VI; Francia. Centre National de la Recherche ...